Changes in HCT and HB response to HIT and HVT - Zinner, C.; Wahl, P.; Haegele, M.; Achtzehn, S.; de Marees, M.; Mester, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Although there is a lively discussion about different physiological effects of high intensity training (HIT) vs. high volume training (HVT), the effects of these two types of training on blood profiles have been payed less attention. Numerous studies examined the response of blood profiles after short term maximal exercise or long-duration exercise, but to the best of our knowledge no study investigated the different response of blood profiles between these two interventions. Therefore the aim of the study was to compare the changes of hematocrit (Hct), haemoglobin (Hb) and plasma volume (PV) after a HIT session and a HVT session. Methods 8 male athletes (27.4 ± 6 years, 182.3 ± 8 cm, 75.6 ± 9 kg, 67.9 ± 4 ml/kg/min) performed two training sessions on a cycle ergometer. The HIT-session consisted of four 30 sec lasting maximal sprints with five minutes rest in between. During the recovery intervals, subjects remained in a sedentary position on the cycle ergometer. The HVT-session consisted of a 60 minute continuous trial at an intensity 41-45% of VO2max. Both sessions started with a warming up of 10 minutes at an intensity of 1.5 Watt/kg bodyweight. Venous blood samples were taken before the warming up and ten minutes after the last sprint and after the 60th minute respectively. Results Hct values showed no significant differences before both sessions (43.0 ± 1.7 % vs. 42.7 ± 1.3 %). After the training Hct values were significantly increased after HIT (46.3 ± 1.7 %), but no significant changes were found after HVT (43.6 ± 1.7 %). Significant changes in the Hb values were also found only after HIT (pre training 14.7 ± 0.6 g/dl vs. post training 15.5 ± 0.6 g/dl) (HVT: pre 14.7 ± 0.5 d/dl, post 15.0 ± 0.7 g/dl). The percentage changes in PV were calculated from hematocrit and haemoglobin values (Dill, 1974). The increments of PV after the two interventions were significantly different (5.9 ± 1.9 % HIT and 1.8 ± 3.6 % HVT). Discussion The small shift of Hct, Hb and PV after HVT could be explained by the water loss during long duration exercise (sweat), but during the HIT session water loss due to sweat can be ruled out. The shift of PV, Hct and Hb after HIT was likely a result of an increased plasma osmotic pressure and local capillary hydrostatic pressure. During HVT sessions, hemodynamic forces are considerably lower than during the HIT sessions. For endurance athletes the WADA defined upper limits for Hct and Hb concentrations to reduce risk of blood manipulations. In this context focus lies on individual blood profiles to get individual Hct and Hb characteristics. Further studies should examine the effects of on PV, Hct and Hb during an interval of HIT and the shift over the time.